Optimalisasi Peran Guru Sebagai Pemimpin Pembelajaran Di Era Digitalisasi Di Yayasan Methodist Berastagi - Heryanto Heryanto; Thomson Siallagan (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This Design-Based Research (DBR) study aims to optimize the role of teachers as instructional leaders through the enhancement of digital pedagogical competencies and transformational learning strategies. The research encompasses needs analysis, seminars, implementation, reflection, and evaluation by integrating technology, pedagogy, content, ethics, and students’ characteristics within the TPACK framework. The study was conducted at the Rahmani Indonesia Methodist Foundation in Berastagi and involved 43 teachers, consisting of 13 elementary school teachers, 13 junior high school teachers, and 17 senior high school teachers. The findings indicate that 92% of the participants demonstrated a strong commitment to improving their digital pedagogical skills, while 88% showed an understanding of digital pedagogical transformation oriented toward learning outcomes. The seminar intervention proved effective in strengthening affective readiness, technical competence, and the transformation of teachers’ roles into facilitators, mentors, innovators, and agents of change in developing digital learning environments that are creative, ethical, adaptive, collaborative, and student-centered.